ANALYSIS OF COMMON SOMATIC MUTATIONS IN COLORECTAL CARCINOMA AND ASSOCIATED DYSREGULATED PATHWAYS - Hassan, Sobia; Khatoon, Ambrina; Bukhari, Uzma; Mirza, Talat (Journal of Ayub Medical College Abbottabad, 2023)
Background: Identification of gene targets and biological pathways involved in colorectal carcinoma (CRC) is essential for better management of patients. Our study aims to highlight common somatic mutations in colorectal carcinoma and to identify dysregulated pathways and gene enrichment based on KRAS and BRAF interaction network analysis. Methods: By using cancer browser tool in COSMIC database, mutation frequencies of the top 20 mutated genes listed for colorectal adenocarcinoma were identified. The most frequent variants of selected genes were explored with ClinVar database which led to identification of protein change along with its cytogenic location, variant type, variant length and the associated single nucleotide polymorphism (SNP). These identified SNPs were searched in Pakistani database using 1000genome in an attempt to identify common polymorphisms. Using the database ClinicalTrial.gov the number of clinical trials based upon these selected mutations was explored. Enrichment and protein interaction (PI) analysis of KRAS and BRAF was carried out to reveal significant biological pathways associated with these genes. Results: In cumulative data, among all variants about 57% of substitution mutations are observed to be G>A including mutations in KRAS, Tp53, SMAD4, PI3K and NRAS. The mutations of KRAS (c.35G>A), TP53 (c.524G>A) and APC (c.4348C>T) were found to be pathogenic with single nucleotide variation and variant length of 1bp. Searching 1000genome database revealed that 100 % of alleles found in East Asian population studied are '˜C'(frequency=1). Significant biological pathways (<0.05) identified by our search include Trk receptor signalling mediated by the MAPK pathway, signalling to p38 via RIT and RIN, signalling to ERKs, Frs2-mediated activation, ARMS-mediated activation and prolonged ERK activation events. Conclusion: Our study highlights the role of genetic profiling in CRC, with emphasis on mutations which may define treatment outcome. Targeting several collateral pathways simultaneously may be further explored to improve colorectal cancer therapeutics.